Robust iterative multiuser receiver for coded CDMA systems in non-Gaussian channels - Ku, Ivan; Lee, Sze Wei; Chuah, Teong Chee (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2007)
A robust front-end pre-filter incorporating non-quadratic signal processing techniques is proposed. We will demonstrate the effectiveness of this filter in suppressing impulsive noises in a coded direct sequence code-division multiple access (DS-CDMA) communication system. Based on M-Estimation approach, the pre-filter works by minimizing an appropriate penalty function in an iterative fashion with minimal increase in computational complexity of the system. With the use of this pre-filter in the system, performance enhancement in excess of 6 dB in non-Gaussian impulsive channels is demonstrated while maintaining comparable performance in Gaussian channel.